Musculoskeletal disorders in Norway: trends in health care utilization and patient pathways: a nationwide register study - Mari Kristine Tyrdal; Flavie Perrier; Cecilie Røe; Bård Natvig; Astrid Klopstad Wahl; Marit B. Veierød; Hilde Stendal Robinson (Scandinavian Journal of Primary Health Care)
Objective Describe trends in health care utilization, demographic characteristics and patient pathways among patients with musculoskeletal disorders (MSD) in Norway.Design Register-based cohort study.Settings Data were obtained from two Norwegian National registries; the Norwegian Control and Payment of Health Reimbursements Database (KUHR) and the Norwegian Patient Registry (NPR).Subjects Patients with MSD according to ICPC-2 and ICD-10 during 2014–2017.Main outcome measures Patient pathways from the first contact and the following two years, described in a Sankey Diagram for all MSD patients and three common diagnoses: spine pain, osteoarthritis (OA) and fibromyalgia (FM).Result About 26% of the Norwegian population consulted PHC annually while 7% were treated in SHC. Mean age was 47 and 53 years in PHC and SHC, respectively. The proportion of women increased by age. Spine pain was the most common diagnosis; 33% and 22% in PHC and SHC, respectively. Over 90% visited a GP first, 50% of them were treated by PT and/or in SHC during follow-up. Patients visiting the PT first were less likely to be treated in SHC. OA patients were most likely to be treated by more than one health care professional (>70%).Conclusion One third of the Norwegian population consulted health care services due to MSD annually between 2014–2017. GP was the most consulted health care professional. Among MSD patients with long-term use of health care services, 50% were treated by a PT and/or in SHC in addition to a GP.